1'-methylspiro[indoline-3,4'-piperidine] Derivatives: Design, Synthesis, Molecular Docking and Anti-tumor Activity Studies - Li, Junjian; Ye, Lianbao; Wang, Yuanyuan; Liu, Ying; Jin, Xiaobao; Li, Ming (Letters in Drug Design & Discovery, 2021)
Background: Spirocyclic indoline compounds widely exist in numerous natural products and synthetic molecules with significant biological activities. In recent years, these kinds of compounds have attracted extensive attention as potent anti-tumor agents in the fields of pharmacology and chemistry. Objective: In this study, we focused on designing and synthesizing novel 1'-methylspiro[indoline- 3,4'-piperidine] derivatives, which were evaluated by preliminary bioactivity experiment in vitro and molecular docking. Materials and Methods: The key intermediate 1'-methylspiro[indoline-3,4'-piperidine] (B4) reacted with benzenesulfonyl chloride with different substituents under alkaline condition to obtain its derivatives (B5-B10). We evaluated their antiproliferative activities against A549, BEL-7402 and HeLa cell lines by MTT assay. We performed the CDOCKER module in Accelrys Discovery Studio 2.5.5 for molecular docking of compound B5, and investigated the binding modes of compound B5 with three different target proteins. Results: The results indicated that compounds B4-B10 exhibited good antiproliferative activities against the above three types of cell lines, in which compound B5 with chloride atom as electronwithdrawing substituent on a phenyl ring showed the highest potency against BEL-7402 cell lines (IC50=30.03±0.43 μg/mL). The results of molecular docking showed that the binding energies of the prominent bioactive compound B5 with CDK, c-Met, and EGFR protein crystals are -44.3583 kcal/mol, -38.3292 kcal/mol, -33.3653 kcal/mol, respectively. Conclusion: 1'-methylspiro[indoline-3,4'-piperidine] and its six derivatives were synthesized and evaluated against BEL-7402, A 549, and Hela cell lines. Compound B5 showed significant inhibition on BEL-7402 cell lines. Molecular docking assays revealed that B5 as a ligand showed strong affinity and appropriate binding pose on the amino acid residues in active sites of the tested targets, which encourage us to conduct further evaluation such as the kinase experiment.
Keywords: cytotoxicity